Spatial and temporal patterns of potassium on grazed permanent pastures – management challenges - Serrano, João (2015)
Alto Alentejo region in Southern Portugal has over 200,000ha of grazing permanent pastures. Here, the soils do not generally need potassium (K) fertilization due to the bedrock richness in K. The general objective of this study was to evaluate the specificity of the spatial and temporal soil K dynamics, over ten years, in a complex agro ecosystem (a bio-diverse pasture installed on a shallow soil, grazed by sheep, in Mediterranean conditions) and the potential for implementing site specific fertilizer management. A 6 ha permanent pasture field was subject to two management systems: a) 2004–2007, the field was used for grazing by sheep and improved by an annual application of super phosphate fertilizer 18%; b) 2007–2013, the field was left fallow. A simplified model, based only on plant K uptake and animal return and losses was used to carry out a K field gate budget estimation. The K spatial trend and K temporal stability were evaluated by a single map of management classes. The evolution of mean soil K concentration in the experimental field over the 10-year study ranges, in relative terms, between -21% and +16% of the overall average of the period considered (96 ± 21 mg kg-1). This behaviour suggests that grazed pastures, as far as the K cycle is concerned, are a “steady state” system. This study, however, shows that the experimental field is dominated by a large spatially anisotropic trend. Significant correlation coefficients were found between the soil K concentration and altimetry (0.614), clay (0.651), sand (-0.674), phosphorus (0.749), organic matter (0.882), apparent soil electrical conductivity (0.436) and pasture dry matter yield (-0.499). It can be stated that the combined effects of an undulated landscape, with sparse trees and animals that selectively graze the plant species and make a heterogeneous deposition of dung and urine, provide a notable spatial variability of soil K concentration (Spatial_ of 29.8 ± 12.3%). The K temporal stability (Temporal_ = 18.1 ± 8.6%), is confirmed by the predominance of moderately stable (56.6% of the experimental field) and of stable areas (25.0% of the experimental field). Within the classes identified as moderately stable and stable, around 45% of the experimental field shows soil K concentrations below average soil K concentration. Based on regional recommendation of 125-150 mg kg-1 of K in the soil to adequately promote the development of dry-land permanent pastures this study demonstrates the interest and the potential for using variable rate technology (VRT) for site-specific K management in pastures in Southern Portugal.